Uncontrolled allergic rhinitis and chronic rhinosinusitis: where do we stand today?. Issue 1 (1st October 2012) - Hellings, P. W.; Fokkens, W. J.; Akdis, C.; Bachert, C.; Cingi, C.; Dietz de Loos, D.; Gevaert, P.; Hox, V.; Kalogjera, L.; Lund, V.; Mullol, J.; Papadopoulos, N. G.; et al.
Abstract: State‐of‐the‐art documents like ARIA and EPOS provide clinicians with evidence‐based treatment algorithms for allergic rhinitis (AR) and chronic rhinosinusitis (CRS), respectively. The currently available medications can alleviate symptoms associated with AR and RS. In real life, a significant percentage of patients with AR and CRS continue to experience bothersome symptoms despite adequate treatment. This group with so‐called severe chronic upper airway disease (SCUAD) represents a therapeutic challenge. The concept of control of disease has only recently been introduced in the field of AR and CRS. In case of poor control of symptoms despite guideline‐directed pharmacotherapy, one needs to consider the presence of SCUAD but also treatment‐related, diagnosis‐related and/or patient‐related factors. Treatment‐related issues of uncontrolled upper airway disease are linked with the correct choice of treatment and route of administration, symptom‐oriented treatment and the evaluation of the need for immunotherapy in allergic patients. The diagnosis of AR and CRS should be reconsidered in case of uncontrolled disease, excluding concomitant anatomic nasal deformities, global airway dysfunction and systemic diseases. Patient‐related issues responsible for the lack of control in chronic upper airway inflammation are often but not always linked with adherence to the prescribed medication and education. This review is an initiative taken by the ENT section of the EAACI in conjunction with ARIA and EPOS experts who felt the need to provide a comprehensive overview of the current state of the art of control in upper airway inflammation and stressing the unmet needs in this domain.